Fatores de risco relacionados à sibilância recorrente do lactente após um ano de idade - Pirtouscheg, Carolina (2024)
Background: Recurrrent wheeze in infants is defined as three episodes of wheeze per year or less in children under five years old and it is a risk fator for future asthma. Objective: To access the risk fators for recurrent wheeze in the second year of life. Methods: Prospective cohort followed 1,176 children from birth through hospital visits and telephone interviews between 12 and 18 months and between 24 and 36 months of age. Results: Recurrent wheeze was identified in 10,2% of the children. Male gender (OR 1,60, 95% IC 1,10 a 2,35), paternal allergic rhinitis (OR 1,88, 95% IC 1,17 a 2,99), paternal asthma (OR 1,84, 95% IC 1,12 a 3,08), asthma in siblings (OR 1,98, 95% IC 1,10 a 3,41), birth in summer (OR 1,94, 95% IC 1,27 a 2,93) birth in spring (OR 1,67, 95% IC 1,07 a 2,60); acute viral bronchiolitis under one year old (OR 4,24, 95% IC 2,80 a 6,48), wheeze under one year old (OR 5,381, 95% IC 3.62-7,95), pneumonia under one year old (OR 2,59, 95% IC 1,07 a 6,51), hospitalization for respiratory disease under one year old (OR 6,03, 95% IC 3,32 a 11,23) and day care attendance (OR 2,36, IC 95% 1,55 a 3,58) in the second year of life are risk factors for recurrent wheeze. Birth in autumn is a protective factor (OR 0,53, IC 95% 0,34 – 0,83). Conclusions: Non-modifiable and modifiable risk factors for recurrent wheeze in infants were found. Prevention of lower respiratory tract infections can reduce recurrent wheeze in infants.